2018
DOI: 10.1021/acscatal.8b02783
|View full text |Cite
|
Sign up to set email alerts
|

Understanding LiOH Formation in a Li-O2 Battery with LiI and H2O Additives

Abstract: LiI-promoted LiOH formation in Li-O 2 batteries with wet ether electrolytes has been investigated by Raman, nuclear magnetic resonance spectroscopy, operando pressure tests, and molecular dynamics simulations. We find that LiOH formation is a synergistic effect involving both H 2 O and LiI additives, whereas with either alone Li 2 O 2 forms. LiOH is generated via a nominal four-electron oxygen reduction reaction, the hydrogen coming from H 2 O and the oxygen from both O 2 and H 2 O, and with fewer side reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
141
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(154 citation statements)
references
References 61 publications
13
141
0
Order By: Relevance
“…[39] Based on our experimental evidences and the lasted literatures, we attributed the O 2 evolution to the redox reaction between iodine species (might be IO − ) with Zn(OH) 2 . [40][41][42][43][44][45] The triiodide, which generated in the cathode side would soon mobile to Zn anode surface and then react with Zn(OH) 2 . When the iodine species diffuse into the depth of passivation region, the Zn(OH) 2 could not be detected in the shallow layer (Figure 1a).…”
Section: −1mentioning
confidence: 99%
“…[39] Based on our experimental evidences and the lasted literatures, we attributed the O 2 evolution to the redox reaction between iodine species (might be IO − ) with Zn(OH) 2 . [40][41][42][43][44][45] The triiodide, which generated in the cathode side would soon mobile to Zn anode surface and then react with Zn(OH) 2 . When the iodine species diffuse into the depth of passivation region, the Zn(OH) 2 could not be detected in the shallow layer (Figure 1a).…”
Section: −1mentioning
confidence: 99%
“…beneficial additive. [15][16][17][18][19][20][21][22][23][24][25] Actually, the influence of water precisely involves the abovementioned key issues: (1) water can alter the rigid surface pathway into solution-mediated Li 2 O 2 nucleated pathway, which obviously enlarges the oxygen reduction reaction (ORR, discharge process) capacity; 16,[18][19][20] (2) proton in water can buffer the violent nucleophilic attack derived from superoxide radical; [26][27][28] and (3) low overpotential can be achieved during oxygen evolution reaction (OER, charge process). 20 Although the introduction of water aggravates Li-metal anode corrosion and there still exists certain dispute toward ORR products component (Li 2 O 2 and/or LiOH), the improvements brought from water are widely recognized as a reformative pathway forward.…”
Section: Context and Scalementioning
confidence: 99%
“…would induce the formation of deposited LiOH. 23,24,57 Recently, since discrepant products and different overpotential have been observed, the water-involved aprotic ORR/OER mechanism still remains a burning issue. Herein, based on the support from comprehensive experimental evidences, we do our best to propose a relatively rational explanation to interpret the intriguing experimental observations and try to make a positive utilization of the observed phenomenon into Li-O 2 battery technology.…”
mentioning
confidence: 99%
“…9,10 Recently, it has been shown that lithium hydroxide (LiOH) can be formed as a discharge product in moisture-tolerant LABs with a high capacity and low charge overpotential using either LiI as a redox mediator or Ru as a catalyst in a wet organic electrolyte. [11][12][13] However, it is widely believed that LiOH is not reversible due to (1) the half-cell potential of the LiOH OER under standard state (aqueous) conditions being higher than that of the Li 2 O 2 OER, given the higher thermodynamic stability of the former; (2) the detection on charge of oxidation products such as…”
Section: Introductionmentioning
confidence: 99%